DEVELOPMENT OF THE TRANSMIGRATION COMMUNITY IN RINGIN JAYA VILLAGE, PULAU BURUNG DISTRICT, INDRAGIRI HILIR DISTRICT, RIAU PROVINCE, 1994-2000 - Rahayu, Sri Budi; Novarianto, Rizki Agung (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Transmigration is the movement of people from a densely populated area to an area that is less or not yet populated. Transmigration in Indonesia has existed since the colonial era and the New Order until now. Transmigration first came to Ringin Jaya Village in 1994. This writing aims to determine the development of the lives of the transmigration community in Ringin Jaya Village. The importance of this research is because the transmigration of people from Java to Ringin Jaya Village has had a very rapid influence on regional expansion, regional development, social and economic development of the people in Ringin Jaya Village. The method used in this research is a qualitative method with a historical approach. Historical research consists of four stages, namely heuristics, source criticism, interpretation, and historiography. Based on the results of initial research, the arrival of the transmigration community in Ringin Jaya Village mostly came from Java. The reason Javanese people participate in transmigration is to look for larger land because the land available in Java is very narrow, while those living in Java have an increasingly dense population and the economy is also difficult, so people participate in transmigration with the aim of changing their lives and making the economy better in the future. which will come.